2017
DOI: 10.1080/17843286.2017.1316005
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine tumor of cecum in patient treated with imatinib mesylate for blastic phase of chronic myeloid leukemia

Abstract: Imatinib mesylate (IM), a tyrosine kinase inhibitor, is the treatment of choice in patients with chronic myeloid leukemia (CML). It is considered a very safe drug, with mostly mild and reversible side effects. Lately, it has been suggested that adverse events may occur after a long term. We report a case of a 72-year-old woman diagnosed with blastic phase of Philadelphia chromosome positive CML treated with IM for 28 months. The patient presented first with ascites as a side effect of the drug. When the ascite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Cases of secondary malignancy are very few in the literature. Secondary primary malignancy of the breast, neuroendocrine tumor of the caecum, squamous cell carcinoma of the skin, acute lymphocytic leukemia have been reported but there has been no case of any benign tumor being reported in the literature [9][10][11]. Elmhadi et al reported a case of successful management of synchronous recurrent breast carcinoma with chronic myelogenous leukemia [12].…”
Section: Discussionmentioning
confidence: 99%
“…Cases of secondary malignancy are very few in the literature. Secondary primary malignancy of the breast, neuroendocrine tumor of the caecum, squamous cell carcinoma of the skin, acute lymphocytic leukemia have been reported but there has been no case of any benign tumor being reported in the literature [9][10][11]. Elmhadi et al reported a case of successful management of synchronous recurrent breast carcinoma with chronic myelogenous leukemia [12].…”
Section: Discussionmentioning
confidence: 99%